Room Temperature Ferromagnetic Properties of Ga14N16−nGd2Cn Monolayers: A First Principle Study - Shijian Tian; Libo Zhang; Yuan Liang; Ruikuan Xie; Li Han; Shiqi Lan; Aijiang Lu; Yan Huang; Huaizhong Xing; Xiaoshuang Chen (Crystals, 2023)
Electronic and magnetic properties of Ga14N16−nGd2Cn monolayers are investigated by means of the first principle calculation. The generalized gradient approximation (GGA) of the density functional theory with the on-site Coulomb energy U was considered (GGA + U). It is found that the total magnetic moment of a Ga14N16Gd2 monolayer is 14 <semantics>μB</semantics> with an antiferromagnetic (AFM) phase. C atom substitutional impurity can effectively change the magnetic state of Ga14N16−nGd2Cn monolayers to ferromagnetic phases (FM), and the magnetic moment increases by 1<semantics>μB</semantics>/1C. The stable FM phase is due to the p-d coupling orbitals between the C-2p and Gd-5d states. Moreover, Curie temperature (TC) close to room temperature (TR, 300 K) is observed in the Ga14N16Gd2C2 monolayer, and the highest value can reach 261.46 K. In addition, the strain effect has a significant positive effect on the <semantics>TC</semantics> of the Ga14N16−nGd2Cn monolayer, which is much higher than the <semantics>TR</semantics>, and the highest value is 525.50 K. This provides an opportunity to further explore the application of two-dimensional magnetic materials in spintronic devices.